Preparation method of vesuvianite coarse aggregate anti-crack Portland cement-based material
By impregnating ammonium dihydrogen phosphate on the volcanic rock aggregate and loading anti-cracking agents with magnesium oxide and stearic acid, the modified crude aggregate is formed, which solves the problem of concrete cracking caused by volcanic rock aggregate and improves the mechanical properties and crack resistance.
Patent Information
- Application Number
- CN202411758599.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
Volcanic stone contains active silica, which causes concrete to easily have microcracks or even cracks in marine or hydropower projects, thereby reducing mechanical properties.
By placing the volcanic stone crude aggregate in a saturated ammonium dihydrogen phosphate solution and loading a carbonaceous anti-cracking agent containing magnesium oxide and stearic acid on its surface, a modified crude aggregate is formed, combining silicate cement-based material to improve the binding force and crack resistance of the aggregate to the matrix.
It effectively alleviates the problem of concrete structure cracking caused by volcanic stone aggregates, improves mechanical strength, and forms a dense and water-repellent isolation layer, prevents the occurrence of alkali aggregate reactions, thereby extending the service life of concrete.
Smart Images

Figure CN119504207A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete material preparation, and in particular to a method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Coarse aggregate is one of the important components of concrete materials, usually pebbles or crushed stones. Among them, pebbles are particles formed by natural weathering, water transportation, sorting and accumulation. Crushed stone is a particle formed by mechanical crushing of natural rocks, pebbles or mine waste rocks. However, with the vigorous development of infrastructure construction in my country in recent years, this type of resources is also rapidly decreasing with continuous mining, and the cost is constantly increasing. Therefore, it is necessary to seek corresponding substitutes to reduce dependence on coarse aggregates of pebbles or crushed stones. Volcanic rock resources are lava formed by the cooling of high-temperature magma erupted from volcanoes, and are potential substitutes for coarse aggregates of pebbles or crushed stones.
[0004] However, the inventors found in actual experiments that, since volcanic rocks contain active silica, the prepared concrete structures are prone to microcracks or even cracks during service when used in marine engineering and hydropower engineering. This is because the silicon and aluminum active minerals (such as cryptocrystalline glassy minerals) in the volcanic rocks react with the sodium and potassium ions provided by the external water environment and the calcium hydroxide produced by cement hydration to form an alkali aggregate reaction. The formed products easily expand after absorbing water, which leads to cracking of the concrete structure and a decrease in mechanical properties. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material, which can effectively alleviate the performance degradation problem caused by cracking of concrete structure caused by volcanic rock aggregate. Specifically, the technical solution of the present invention is as follows.
[0006] A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material comprises the following steps: (1) The volcanic rock coarse aggregate is immersed in a saturated ammonium dihydrogen phosphate solution, and then the coarse aggregate is taken out and dried to obtain the pretreated aggregate.
[0007] (2) Mix the carbon powder with a solution containing a saturated magnesium ion source, and then add ammonia water to mix. After completion, the obtained mixture is pyrolyzed in a protective atmosphere to form magnesium oxide to obtain pretreated carbon powder.
[0008] (3) The pretreated carbon powder and molten stearic acid are mixed and heated and kept warm, and then cooled to room temperature and ground to obtain an anti-cracking agent.
[0009] (4) adding the anti-cracking agent to the pretreated aggregate whose surface is moistened with an anhydrous solvent under stirring conditions, mixing the mixture, and then heating the mixture to a temperature above the melting point of the stearic acid and keeping the temperature, and then cooling the mixture to room temperature to obtain a modified coarse aggregate.
[0010] (5) Mixing silicate cement, the modified coarse aggregate, fine aggregate, filler, silica fume and water reducing agent, and then adding water to mix evenly to obtain the cement-based material.
[0011] Furthermore, in step (1), the ratio of the volcanic rock coarse aggregate to the saturated diammonium phosphate solution is 1 g: 8-20 ml. Optionally, the particle size of the volcanic rock coarse aggregate is 5-15 mm.
[0012] Furthermore, in step (1), the immersion time is 40 to 60 minutes.
[0013] Furthermore, in step (1), the drying temperature is 70-90° C. and the drying time is 1-2 hours.
[0014] Furthermore, in step (2), the ratio of the carbon powder to the solution containing a saturated magnesium ion source is 1 g: 1-2.5 ml. Optionally, the magnesium ion source includes at least one of magnesium sulfate and magnesium nitrate.
[0015] Further, in step (2), according to OH - :Mg 2+ The ammonia water is added in a ratio of molar ratio = 1~1.2:1.
[0016] Furthermore, in step (2), the pyrolysis temperature is 450-550° C. and the time is 20-30 min. Optionally, the protective atmosphere includes any one of nitrogen, argon, etc.
[0017] Furthermore, in step (3), the mass ratio of the pretreated carbon powder to stearic acid is 1:0.4-0.6.
[0018] Furthermore, in step (3), the heating temperature is 75-80°C, the holding time is 5-10 minutes, and stirring is continued during the holding process. This step utilizes the melting property of stearic acid to store stearic acid and magnesium oxide in the carbon powder, and facilitates the formation of the anti-cracking agent to be bonded to the surface of the volcanic rock coarse aggregate.
[0019] Furthermore, in step (3), the anti-cracking agent has a fineness of 100-180 mesh.
[0020] Furthermore, in step (4), the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:20-32.
[0021] Furthermore, in step (4), the ratio of the pretreated aggregate to the anhydrous solvent is 1 g: 0.3-0.5 ml. Optionally, the anhydrous solvent includes at least one of anhydrous methanol and anhydrous ethanol.
[0022] Furthermore, in step (4), the heating temperature is 75-80° C. and the insulation time is 10-15 min.
[0023] Furthermore, in step (5), the ratio of the silicate cement, the modified coarse aggregate, the fine aggregate, the filler, silica fume, the water reducer and the water is 160-200 parts by weight: 420-550 parts by weight: 280-330 parts by weight: 13-20 parts by weight: 15-25 parts by weight: 2.4-3.7 parts by weight: 73-100 parts by weight.
[0024] Furthermore, in step (5), the filler includes at least one of fly ash, calcium carbonate powder, shell powder, mica powder, etc. Optionally, the particle size of the filler is 200-300 meshes.
[0025] Furthermore, in step (5), the water reducer includes at least one of a polycarboxylic acid water reducer, a naphthalene-based water reducer, a lignin sulfonate water reducer, a melamine-based water reducer, and the like.
[0026] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: The present invention first utilizes the characteristic of volcanic rock containing a large number of pores to load diammonium phosphate in it to form a pretreated aggregate. Then, a carbonaceous anti-cracking agent containing magnesium oxide and stearic acid is also loaded on the surface of the aggregate, which effectively alleviates the performance degradation problem caused by cracking of the concrete structure caused by the volcanic rock aggregate. This is because: on the one hand, the magnesium oxide in the anti-cracking agent and the diammonium phosphate dissolved in the volcanic rock coarse aggregate undergo a hydration reaction to form a high-strength, high-viscosity and dense hydration product struvite. At the same time, the stearic acid reacts with the alkaline environment (OH) formed by cement hydration. -) reacts with calcium ions to form a calcium stearate solid water repellent, which is cemented and mixed with the hydration product struvite, which not only helps to improve the bonding force between the volcanic stone coarse aggregate and the cement-based material matrix, thereby improving the mechanical strength, but also plays a role in forming a dense, water-repellent, high-strength and high-viscosity isolation layer on the surface of the aggregate, thereby helping to prevent the cement hydration product calcium hydroxide and the sodium / potassium ions in the external water environment from entering the aggregate to form expansive products for alkali-aggregate reaction, causing microcracks or even cracking. At the same time, the formation of calcium stearate consumes the calcium hydroxide around the aggregate, thereby weakening the material conditions for alkali-aggregate reaction. The carbon particles in the anti-cracking agent can also play a role in adsorbing sodium / potassium ions, thereby reducing the entry of sodium / potassium ions into the aggregate. In addition, since the calcium stearate water repellent effectively improves the water resistance of the isolation layer, the durability of the isolation layer is improved. On the other hand, the ammonium dihydrogen phosphate in the volcanic stone aggregate can further react preferentially with the hydration product calcium hydroxide that enters, thereby consuming the reaction product before the alkali-aggregate reaction starts. At the same time, the solid particles of calcium dihydrogen phosphate formed by the reaction are filled in the pores of the volcanic rock aggregate for compaction, which helps to further reduce the entry of hydration products such as calcium hydroxide and reduce the occurrence of alkali-aggregate reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] It should be noted that the drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention.
[0028] Figure 1 A sample of pretreated aggregate prepared in Example 1 below.
[0029] Figure 2 This is a sample picture of the pre-treated carbon powder prepared in Example 1 below.
[0030] Figure 3 This is a test chart of the compressive strength test of the following Example 1. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. The reagents or raw materials used in the invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or are used according to the product specification. Now the technical scheme of the present invention is further described in conjunction with specific embodiments.
[0032] Example 1 A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material comprises the following steps: (1) Mix volcanic rock coarse aggregate with a particle size distribution between 5 and 10 mm with saturated ammonium dihydrogen phosphate solution at a ratio of 1 g:15 ml and stir evenly, then soak for 40 minutes. After completion, filter out the coarse aggregate, heat to 90°C and dry for 1 hour to obtain the pretreated aggregate. Figure 1 shown.
[0033] (2) Mix the carbon powder and saturated magnesium sulfate solution at a ratio of 1g:2ml and stir evenly. - :Mg 2+ The molar ratio of is 1.1:1, 10% ammonia water is added, and after stirring evenly, the obtained mixture is evaporated to remove moisture, and then heated to 530℃ in a nitrogen atmosphere for 25min, and then cooled to room temperature to obtain pretreated carbon powder, such as Figure 2 shown.
[0034] (3) The pretreated carbon powder and molten stearic acid are mixed in a mass ratio of 1:0.6 and stirred evenly, and then heated to 80°C and kept warm for 5 minutes, and stirred continuously during the heat preservation process. After completion, the mixture is cooled to room temperature and ground, and sieved to obtain an anti-cracking agent with a fineness of 120 mesh.
[0035] (4) Spray anhydrous ethanol onto the pretreated aggregate of this embodiment while stirring (the ratio of the two is 0.4 ml: 1 g), stir evenly and continue to add the anti-cracking agent of this embodiment, and the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:25, stir evenly and heat to 80°C and keep warm for 10 minutes, and then cool to room temperature to obtain modified coarse aggregate.
[0036] (5) Take 172 parts by weight of 42.5 ordinary Portland cement, 480 parts by weight of the modified coarse aggregate, 300 parts by weight of river sand (medium sand) fine aggregate, 16 parts by weight of 200-mesh calcium carbonate powder, 19 parts by weight of silica fume, and 3.2 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir evenly, then add 82.5 parts by weight of clean water and stir evenly to obtain a cement-based material.
[0037] The cement-based material prepared in this embodiment was made into a test piece, and then immersed in a 3.5% sodium chloride solution for 14 days. Then, the compressive strength of the test piece was tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 3 As shown, the result is 47.33MPa.
[0038] Example 2 A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material comprises the following steps: (1) Mix volcanic rock coarse aggregate with a particle size distribution between 10 and 15 mm with saturated diammonium phosphate solution at a ratio of 1 g:20 ml and stir evenly, then soak for 50 minutes. After completion, filter out the coarse aggregate, heat to 80°C and dry for 2 hours to obtain pretreated aggregate.
[0039] (2) Mix the carbon powder and saturated magnesium nitrate solution at a ratio of 1g:2.5ml and stir evenly. - :Mg 2+ A 10% mass fraction of ammonia water is added at a molar ratio of 1.2:1, and the mixture is evaporated to remove moisture after being stirred evenly. It is then heated to 550°C in a nitrogen atmosphere and kept warm for 20 minutes. After completion, it is cooled to room temperature to obtain pretreated carbon powder.
[0040] (3) The pretreated carbon powder and molten stearic acid are mixed in a mass ratio of 1:0.4 and stirred evenly, and then heated to 75°C and kept warm for 8 minutes, and stirred continuously during the heat preservation process. After completion, the mixture is cooled to room temperature and ground, and sieved to obtain an anti-cracking agent with a fineness of 100 mesh.
[0041] (4) Spray anhydrous ethanol onto the pretreated aggregate of this embodiment while stirring (the ratio of the two is 0.3 ml: 1 g), and continue to add the anti-cracking agent of this embodiment after stirring evenly, and the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:32. After stirring evenly, heat to 75°C and keep warm for 15 minutes. After completion, cool to room temperature to obtain modified coarse aggregate.
[0042] (5) Take 160 parts by weight of 42.5 ordinary Portland cement, 420 parts by weight of the modified coarse aggregate, 280 parts by weight of river sand (medium sand) fine aggregate, 13 parts by weight of 200-mesh shell powder, 15 parts by weight of silica fume, and 2.4 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir evenly, then add 73 parts by weight of clean water and stir evenly to obtain a cement-based material.
[0043] The cement-based material prepared in this embodiment was made into a test piece, and then immersed in a 3.5% sodium chloride solution for 14 days. The compressive strength of the test piece was then tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), and the result was 45.08 MPa.
[0044] Example 3 A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material comprises the following steps: (1) Mix volcanic rock coarse aggregate with a particle size distribution between 7 and 12 mm with saturated diammonium phosphate solution at a ratio of 1 g:8 ml and stir evenly, then soak for 60 minutes. After completion, filter out the coarse aggregate, heat to 70°C and dry for 1.5 hours to obtain pretreated aggregate.
[0045] (2) Mix the carbon powder and saturated magnesium sulfate solution at a ratio of 1g:1ml and stir evenly. - :Mg 2+ A 10% mass fraction of ammonia water is added at a molar ratio of 1:1, and the mixture is evaporated to remove moisture after being stirred evenly. It is then heated to 450°C in a nitrogen atmosphere and kept warm for 30 minutes. After completion, it is cooled to room temperature to obtain pretreated carbon powder.
[0046] (3) The pretreated carbon powder and molten stearic acid are mixed in a mass ratio of 1:0.5 and stirred evenly, and then heated to 80°C and kept warm for 10 minutes, and stirred continuously during the heat preservation process. After completion, the mixture is cooled to room temperature and ground, and sieved to obtain an anti-cracking agent with a fineness of 180 mesh.
[0047] (4) Spray anhydrous methanol onto the pretreated aggregate of this embodiment while stirring (the ratio of the two is 0.5 ml: 1 g), stir evenly and continue to add the anti-cracking agent of this embodiment, and the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:20, stir evenly and heat to 75°C and keep warm for 15 minutes, and then cool to room temperature to obtain modified coarse aggregate.
[0048] (5) Take 200 parts by weight of 42.5 ordinary Portland cement, 550 parts by weight of the modified coarse aggregate, 330 parts by weight of river sand (medium sand) fine aggregate, 20 parts by weight of 300-mesh mica powder, 25 parts by weight of silica fume, and 3.7 parts by weight of sodium lignin sulfonate water reducer. Mix the above raw materials and stir evenly, then add 100 parts by weight of clean water and stir evenly to obtain a cement-based material.
[0049] The cement-based material prepared in this embodiment was made into a test piece, and then immersed in a 3.5% sodium chloride solution for 14 days. The compressive strength of the test piece was then tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), and the result was 48.62 MPa.
[0050] Example 4 A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material comprises the following steps: (1) Spray anhydrous ethanol onto volcanic rock coarse aggregate with a particle size distribution between 5 and 10 mm while stirring (the ratio of the two is 0.4 ml: 1 g), stir evenly and continue to add the anti-cracking agent prepared in Example 1, and the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:25. After stirring evenly, heat to 80°C and keep warm for 10 minutes. After completion, cool to room temperature to obtain modified coarse aggregate.
[0051] (2) Take 172 parts by weight of 42.5 ordinary Portland cement, 480 parts by weight of the modified coarse aggregate, 300 parts by weight of river sand (medium sand) fine aggregate, 16 parts by weight of 200-mesh calcium carbonate powder, 19 parts by weight of silica fume, and 3.2 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir evenly, then add 82.5 parts by weight of clean water and stir evenly to obtain a cement-based material.
[0052] The cement-based material prepared in this embodiment was made into a test piece, and then immersed in a 3.5% sodium chloride solution for 14 days. The compressive strength of the test piece was then tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), and the result was 30.17 MPa.
[0053] Example 5 A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material comprises the following steps: (1) Mix volcanic rock coarse aggregate with a particle size distribution between 7 and 12 mm with saturated diammonium phosphate solution at a ratio of 1 g:8 ml and stir evenly, then soak for 60 minutes. After completion, filter out the coarse aggregate, heat to 70°C and dry for 1.5 hours to obtain pretreated aggregate.
[0054] (2) Mix the carbon powder and molten stearic acid in a mass ratio of 1:0.5 and stir evenly, then heat to 80°C and keep warm for 10 minutes, stirring continuously during the heat preservation process. After completion, cool to room temperature and grind, and sieve to obtain an anti-cracking agent with a fineness of 180 mesh.
[0055] (3) Spray anhydrous methanol onto the pretreated aggregate of this embodiment while stirring (the ratio of the two is 0.5 ml: 1 g), stir evenly and continue to add the anti-cracking agent of this embodiment, and the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:20, stir evenly and heat to 75°C and keep warm for 15 minutes, and then cool to room temperature to obtain modified coarse aggregate.
[0056] (4) Take 200 parts by weight of 42.5 ordinary Portland cement, 550 parts by weight of the modified coarse aggregate, 330 parts by weight of river sand (medium sand) fine aggregate, 20 parts by weight of 300-mesh mica powder, 25 parts by weight of silica fume, and 3.7 parts by weight of sodium lignin sulfonate water reducer. Mix the above raw materials and stir evenly, then add 100 parts by weight of clean water and stir evenly to obtain a cement-based material.
[0057] The cement-based material prepared in this embodiment was made into a test piece, and then immersed in a 3.5% sodium chloride solution for 14 days. The compressive strength of the test piece was then tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), and the result was 35.21 MPa.
[0058] Example 6 A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material comprises the following steps: (1) Mix volcanic rock coarse aggregate with a particle size distribution between 10 and 15 mm with saturated diammonium phosphate solution at a ratio of 1 g:20 ml and stir evenly, then soak for 50 minutes. After completion, filter out the coarse aggregate, heat to 80°C and dry for 2 hours to obtain pretreated aggregate.
[0059] (2) Mix the carbon powder and saturated magnesium nitrate solution at a ratio of 1g:2.5ml and stir evenly. - :Mg 2+ The molar ratio of the mixture is 1.2:1, and 10% ammonia water by mass is added. After stirring evenly, the mixture is evaporated to remove moisture, and then heated to 550°C in a nitrogen atmosphere and kept warm for 20 minutes. After completion, it is cooled to room temperature and ground. After sieving, an anti-cracking agent with a fineness of 100 mesh is obtained.
[0060] (3) Spray anhydrous ethanol onto the pretreated aggregate of this embodiment while stirring (the ratio of the two is 0.3 ml: 1 g), and continue to add the anti-cracking agent of this embodiment after stirring evenly, and the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:32. After stirring evenly, heat to 75°C and keep warm for 15 minutes. After completion, cool to room temperature to obtain modified coarse aggregate.
[0061] (4) Take 160 parts by weight of 42.5 ordinary Portland cement, 420 parts by weight of the modified coarse aggregate, 280 parts by weight of river sand (medium sand) fine aggregate, 13 parts by weight of 200-mesh shell powder, 15 parts by weight of silica fume, and 2.4 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir evenly, then add 73 parts by weight of clean water and stir evenly to obtain a cement-based material.
[0062] The cement-based material prepared in this embodiment was made into a test piece, and then immersed in a 3.5% sodium chloride solution for 14 days. The compressive strength of the test piece was then tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), and the result was 36.49 MPa.
[0063] Example 7 A method for preparing a volcanic rock coarse aggregate silicate cement-based material comprises the following steps: Take 172 parts by weight of 42.5 ordinary Portland cement, 480 parts by weight of volcanic rock coarse aggregate with a particle size distribution between 5 and 10 mm, 300 parts by weight of river sand (medium sand) fine aggregate, 16 parts by weight of 200-mesh calcium carbonate powder, 19 parts by weight of silica fume, and 3.2 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir evenly, then add 82.5 parts by weight of clean water and stir evenly to obtain cement-based material.
[0064] The cement-based material prepared in this embodiment was made into a test piece, and then immersed in a 3.5% sodium chloride solution for 14 days. The compressive strength of the test piece was then tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), and the result was 24.87 MPa.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a volcanic rock coarse aggregate crack-resistant silicate cement-based material, characterized in that: The steps include: (1) immersing the volcanic rock coarse aggregate in a saturated diammonium phosphate solution, and then taking out the coarse aggregate and drying it to obtain the pretreated aggregate; (2) mixing the carbon powder with a solution containing a saturated magnesium ion source, and then adding ammonia water to mix; after completion, pyrolyzing the obtained mixture in a protective atmosphere to form magnesium oxide to obtain pretreated carbon powder; (3) mixing the pretreated carbon powder and molten stearic acid, heating and keeping the mixture warm, and then cooling the mixture to room temperature and grinding the mixture to obtain an anti-cracking agent; (4) adding the anti-cracking agent to the pretreated aggregate whose surface is wetted with an anhydrous solvent under stirring conditions, mixing the mixture, then heating the mixture to a temperature above the melting point of the stearic acid and keeping the mixture warm, and then cooling the mixture to room temperature to obtain a modified coarse aggregate; (5) Mixing silicate cement, the modified coarse aggregate, fine aggregate, filler, silica fume and water reducing agent, and then adding water to mix evenly to obtain the cement-based material.
2. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (1), the ratio of the volcanic rock coarse aggregate to the saturated diammonium phosphate solution is 1g: 8-20ml; Optionally, in step (1), the immersion time is 40 to 60 minutes; Optionally, in step (1), the particle size of the volcanic rock coarse aggregate is 5 to 15 mm; Optionally, in step (1), the drying temperature is 70-90° C. and the drying time is 1-2 hours.
3. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (2), the ratio of the carbon powder to the solution containing a saturated magnesium ion source is 1 g: 1-2.5 ml; optionally, the magnesium ion source includes at least one of magnesium sulfate and magnesium nitrate.
4. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (2), according to OH - :Mg 2+ The ammonia water is added in a ratio of molar ratio = 1~1.2:
1.
5. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (2), the pyrolysis temperature is 450-550°C and the time is 20-30 minutes; Optionally, in step (2), the protective atmosphere includes any one of nitrogen and argon.
6. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (3), the mass ratio of the pretreated carbon powder to stearic acid is 1:0.4-0.6; Optionally, in step (3), the heating temperature is 75-80°C, the insulation time is 5-10 min, and stirring is continued during the insulation process; Optionally, in step (3), the anti-cracking agent has a fineness of 100-180 mesh.
7. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (4), the mass ratio of the anti-cracking agent to the pretreated aggregate is 1:20-32.
8. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (4), the ratio of the pretreated aggregate to the anhydrous solvent is 1 g: 0.3-0.5 ml; Optionally, in step (4), the anhydrous solvent includes at least one of anhydrous methanol and anhydrous ethanol; Optionally, in step (4), the heating temperature is 75-80° C. and the insulation time is 10-15 min.
9. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to claim 1, characterized in that: In step (5), the ratio of the silicate cement, the modified coarse aggregate, the fine aggregate, the filler, the silica fume, the water reducer and the water is 160-200 parts by weight: 420-550 parts by weight: 280-330 parts by weight: 13-20 parts by weight: 15-25 parts by weight: 2.4-3.7 parts by weight: 73-100 parts by weight.
10. The method for preparing the volcanic rock coarse aggregate crack-resistant silicate cement-based material according to any one of claims 1 to 9, characterized in that: In step (5), the filler includes at least one of fly ash, calcium carbonate powder, shell powder, and mica powder; Optionally, in step (5), the particle size of the filler is 200-300 mesh; Optionally, in step (5), the water reducer includes at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, a lignin sulfonate water reducer, and a melamine-based water reducer.
Citation Information
Cited By
Preparation method of early-strength carbon-reduction lightweight aggregate cement-based material
CN121698611A
Preparation method of early-strength carbon-reduced lightweight aggregate cement-based material
CN121698611B